FEASIBILITY ANALYSIS OF CHILD-FRIENDLY DISASTER RESPONSE EDUCATIONAL COMICS AS A SOCIAL STUDY LEARNING MEDIUM IN ELEMENTARY SCHOOLS - Ika Ari Pratiwi; Eko Handoyo; Ani Rusilowati; Trimurtini Trimurtini (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Flood disasters remain a major challenge in elementary schools in the Kudus area, while disaster mitigation learning in social studies has not been optimally implemented. This condition leads to limited student understanding of risks and disaster response measures. This study aims to analyze the feasibility of the child-friendly educational comic "Sahabat Alam Tanggap Banjir di Kampung Kesambi" as a social studies learning medium for fourth-grade elementary school students. This research method uses a research and development (R&D) approach, with the ADDIE model applied through the development stage. The comic was validated by material, media, and language experts using a Likert-scale instrument and then analyzed using a feasibility percentage conversion. The results showed a very high level of feasibility, with material validity of 94.4%, media validity of 95.8%, and language validity of 95.1%. This comic presents the flood phenomenon, its causes, and mitigation measures in a coherent, contextually relevant manner, tailored to students’ characteristics. In addition, the comic also integrates social studies concepts such as human relationships with the environment, mutual cooperation, and environmental awareness. These findings indicate that child-friendly disaster response educational comics are highly suitable for use as social studies learning media in elementary schools. Comics not only support disaster literacy but also have the potential to enhance critical thinking skills and foster environmentally conscious character in students. The implications of this research suggest that child-friendly educational comics can strengthen contextual social studies learning and potentially enhance students' critical thinking skills and environmental character.